Characters of Early Childhood Manners in The Storybook Permisi - Riska Nofianti, Farhati; Wachid Bambang Suharto, Abdul; Saputra, Rizki (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This research examines the story of Excuse me book from the aspect of polite character for early childhood. Storybooks are one of the interesting media to instill in early childhood. The purpose of this study was to analyze the character of manners in early childhood in the story book entitled